Entre o medo e a alegria: a retórica, as paixões e o lúdico nas oficinas pedagógicas - Pereira, Maria de Lourdes e Silva (2014)
The theme of this work the rhetoric, the passions and the playful on the textual production originated from the experience, while Portuguese language professor, with students of the College. The research aimed to verify why some college students feel displeasure in the activities of reading and writing and what are the possible ways to reverse this feeling. It began with a diagnostic questionnaire about their habits, tastes and feelings of students in relation to the acts of reading and writing. The answers to this questionnaire have shown that the reason for the resistance to these activities is the fear or misgiving passion linked to dysphoric sadness - that affects people who have been through unpleasant situations that caused them grief. The passions, in general, have their contraries. The affections contrary to fear or misgiving are the hope, the courage and the confidence elated passions linked to joy. A passion, if considered indomitable, requires action. On this finding, the best way to act to curb the sad feelings and awaken the joy, was to introduce the playfulness in the textual production activities. These activities have been developed in the form of educational workshops, democratic spaces that provide reflection, Exchange and creation process. Four workshops were offered for three different groups in different colleges outside the regular schedule of classes; with the exception of a class, whose workload was from Monday to Saturday, so the students have developed activities in the regular lessons of Portuguese language. The rhetoric, has always presented in the practices of human life, was informed theoretically by Perelman and Olbrechts-Tyteca (1999), Reboul (1998) and Meyer (2007). The passions were studied on the basis of some philosophers, such as Aristotle (2000), Hobbes (1999, 2009), Descartes (1999) and Espinosa (2012, 2013). Huizinga (2012), Kishimoto (2011, 2012) and Bachelard (1988) guided the reflections about the playful. Studies on the writing were guided by Barthes (1971, 1975, 1977, 1980, 2012), Serafini (2000), Koch and Elias (2007, 2009) and Passarelli (2004). The self-evaluations made by students, after the workshops, has confirmed the postulates of the authors studied: that a good passion can combat a bad passion and playfulness is essential in human life and awaken creativity which falls asleep in every person